Characteristics of Type 2 Diabetes Mellitus Patients With Diabetic Ketoacidosis: A Study in A National Referral Hospital in Indonesia - Fuada, Afifah Annis; Aprilia, Dinda; Putri, Biomechy Oktomalio (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: Diabetic ketoacidosis (DKA) is one of the acute complication of diabetes mellitus (DM) with high mortality and morbidity rates. Research data regarding the characteristics of patients with type 2 diabetes mellitus (T2DM) with and without DKA are not yet widely available. Therefore, further research is needed to minimize the annual morbidity and mortality rate and prevent complications at the earliest possible moment. This study was carried out to determine the differences in the characteristics of T2DM patients with and without DKA in Dr. M. Djamil Central General Hospital Padang period 1st January 2018 to 31stDecember 2020. Methods: This study used a comparative analytic study with a cross-sectional approach using the medical records of T2DM patients with and without DKA in Dr. M. Djamil Central General Hospital Padang period 1st January to 31st December 2020 with total sampling. Data analysis calculated by chi-square test, unpaired T-test, and Mann-Whitney test. Results: Most of T2DM patients with DKA were aged ≥ 40 years (62.1%), female (65.5%), secondary level of education (72.4%), DM diagnosis duration was ≤ 5 years (75.9%), had infection precipitating factors (65.5%), on insulin (58.6%), Body Mass Index (BMI) in overweight-obese criteria (55%), fasting blood glucose (FBG) < 250 mg/dl (62.1%), and post-prandial glucose (PPG) 250-600 mg/dl (51.7%). This study found that the association of age, DM diagnosis duration, precipitating factors, medication use, and PPG with DKA in T2DM patients (p<0.05). Conclusion: This study confirmed significant differences in age, DM diagnosis duration, precipitation factors, type of antidiabetic therapy, and PPG between T2DM patients with and without DKA in Dr. M. Djamil Central General Hospital Padang.